The Hyperpolarization-Activated HCN4 Channel is Important for Proper Maintenance of Oscillatory Activity in the Thalamocortical System - Zobeiri, Mehrnoush; Chaudhary, Rahul; Blaich, Anne; Rottmann, Matthias; Herrmann, Stefan; Meuth, Patrick; Bista, Pawan; Kanyshkova, Tatyana; Lüttjohann, Annika; Narayanan, Venu; Hundehege, Petra; Meuth, Sven G.; et al. (Cerebral Cortex, 2019)
Hyperpolarization-activated cation channels are involved, among other functions, in learning and memory, control of synaptic transmission and epileptogenesis. The importance of the HCN1 and HCN2 isoforms for brain function has been demonstrated, while the role of HCN4, the third major neuronal HCN subunit, is not known. Here we show that HCN4 is essential for oscillatory activity in the thalamocortical (TC) network. HCN4 is selectively expressed in various thalamic nuclei, excluding the thalamic reticular nucleus. HCN4-deficient TC neurons revealed a massive reduction of Ih and strongly reduced intrinsic burst firing, whereas the current was normal in cortical pyramidal neurons. In addition, evoked bursting in a thalamic slice preparation was strongly reduced in the mutant mice probes. HCN4-deficiency also significantly slowed down thalamic and cortical oscillations during active wakefulness. Taken together, these results establish that thalamic HCN4 channels are essential for the production of rhythmic intrathalamic oscillations and determine regular TC oscillatory activity during alert states.
CRIS-Team Scopus Importer:2019-07-16
Keywords: HCN4 channels; HCN4 knock out mice; Ih; thalamocortical dysrhythmia; thalamocortical oscillations